THE ABUNDANCE OF ANTS (FORMICIDAE) IN COFFEE PLANTATIONS OF MERAPI, LAHAT DISTRICT - Novin Teristiandi; Meta Yuliana (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2025)
Ants are widely used as ecological indicators in agricultural landscapes, yet community responses can vary across local environmental gradients. This study assessed ground-active ant assemblages in coffee plantations in Merapi, Lahat (South Sumatra, Indonesia) at sites categorized as near versus far from a coal-mining area, using pitfall traps and community-level metrics. Mean temperatures during sampling were nearly identical between site categories (near 30.54 °C; far 30.56 °C). Ant assemblages showed contrasting patterns in richness and abundance: far sites contained six taxa but a lower total number of individuals (117), while near sites contained three taxa but higher total abundance (209). Species composition differed markedly, with far sites dominated by Solenopsis invicta and near sites dominated by Leptogenys sp. and Myopias emeryi. Diversity indices reflected these patterns: Shannon diversity was higher far from the mine (0.8906) than near (0.7215), while Simpson dominance was slightly higher far (0.5607) than near (0.5219), and evenness was higher near (0.6567) than far (0.4971). These findings indicate an association between distance class and ant community structure in coffee plantations, characterized by higher richness but stronger dominance at far sites and higher abundance but lower richness at near sites; however, conclusions about mining impacts should remain cautious given the observational design.